Analysis of Issuers' Financial Factors on the Value of Start-up Companies in Indonesia - Kadar Nurjaman (Budapest International Research and Critics University, 2022)
This study aims to analyze the financial factors of issuers on the value of startup companies in Indonesia. This research uses quantitative research with a causal approach. The research was conducted on Indonesian startup companies, namely GoTo, Tokopedia, OVO, Bukalapak, J&T Express, and Traveloka. Research variables are divided into two categories, namely predictor variables (Profitability, Liquidity, and Leverage) and effect variables (Company Value). The data used in this study is secondary data derived from the company's 2017-2020 annual financial statements. The study data are analyzed utilizing multiple linear regression techniques, classical assumption tests (autocorrelation, normality, and multicollinearity tests), and hypothesis testing. Profitability, liquidity, and leverage all have a positive and considerable effect on business value, according to research and analysis.